Tobacco control challenges in China: Big data analysis of online tobacco marketing information - Xiuli Wang; Ying Xiong; Wenwen Zhao (Elsevier, 2020)
Objective: To develop tobacco control strategies by analyzing online tobacco marketing information in China. Methods: Using web-crawler software, this study acquired 106,485 pieces of online tobacco marketing information published on 11 different Internet platforms including Weibo, WeChat, Baidu, etc., from January-June 2018. The data were used to investigate the characteristics and social networks of online tobacco marketing via content and social network analysis. Results: The total volume of online tobacco marketing during the study period was high, showing a positive trend. Of all the marketing subjects, those involving "flavor capsule", "Marlboro", and "Esse" were the most popular. The Weibo platform had the highest volume of online tobacco marketing information as well as the largest proportion of explicit marketing information. This was followed by other social media platforms such as Baidu Search, Baidu Tieba, and Xiaohongshu, where implicit marketing information predominated. The overall network structure of tobacco websites exhibited a significant centralization feature, where traditional and novel tobacco websites formed two clusters with almost no intersections. The China Tobacco Science and Education Website (http://www.tobaccoinfo.com.cn/) and E-Cigarette Home (http://ecigm.com/) were the two nodes of the highest degree centrality within the respective "circle", while the China Tobacco Monopoly Bureau Website (http://www.tobacco.gov.cn/) was the node with the highest closeness centrality. By contrast, Baidu Tieba's overall network structure was more decentralized, and the degree of correlation between different nodes was relatively low. Conclusion: Online tobacco marketing demonstrated high volumes and wide coverage, and an intertwined network, thereby creating major obstacles for tobacco control. To address this issue, the government should strengthen network supervision of tobacco marketing and revise its current regulations. Meanwhile, Internet platforms should improve self-regulation by comprehensively removing and blocking tobacco-related information. Lastly, the media and public should advocate associated policies and support Internet platform supervision.